Abdominal Aortic Aneurysm: a review on the role of oral antidiabetic drugs. - Susana Melissa Ribeiro da Silva (2020)
INTRODUCTIONː A paradoxical negative association between Diabetes Mellitus and Abdominal Aortic Aneurysm(AAA) prevalence and growth is established. However, so far is not possible to determine whether this protection comes from the disease itself or the medication for Diabetes. The aim of this manuscript is to review the association between oral antidiabetic drugs and AAA incidence and growth. EVIDENCE ACQUISITIONː A search was conducted on Pubmed and Scopus databases until December 2019 to identify publications reporting on the association between oral antidiabetic drugs (biguanides/metformin, sulfonylureas(SU), thiazolidinediones(TZD), dipeptidyl-peptidase 4(DPP-4) inhibitors, glucagon-like peptide 1(GLP-1) agonists, sodium-glucose transporter protein-2(SGLT2) inhibitors) and the outcomes AAA incidence and growth. Only data from human studies were considered, with a minimum of 3 months follow-up. EVIDENCE SYNTHESISː Six studies enrolling 25810 patients were included: one reporting on the AAA risk and five reporting on AAA growth. Metformin prescription was associated with a 28% reduction in AAA occurrence, while SU and TZD were associated with a 18% decrease in AAA risk. Regarding AAA enlargement, results were concordant for a slower expansion rate associated with metformin, with a decrease ranging from -0.30 mm/y to -1.30 mm/y, but not consistent for other antidiabetic drugs. CONCLUSIONSː Metformin seems to be associated with a decrease in AAA risk and enlargement rate. Evidence for the other classes is lacking. Studies evaluating the association between oral antidiabetic drugs and AAA progression, independently of the diabetic status, are needed.